Guilingji Protects Against Spermatogenesis Dysfunction From Oxidative Stress via Regulation of MAPK and Apoptotic Signaling Pathways in Immp2l Mutant Mice - Wang, Zhenqing; Xie, Yun; Chen, Haicheng; Yao, Jiahui; Lv, Linyan; Li, Yanqing; Deng, Chunhua; Zhang, Min; Sun, Xiangzhou; Liu, Guihua (Frontiers in Pharmacology, 2022)
Male infertility is a major health issue with an estimated prevalence of 4.2% of male infertility worldwide. Oxidative stress (OS), characterized by an overabundance of reactive oxygen species (ROS) or a deficiency of antioxidants, is one of the major causes of male infertility. Meanwhile, oxidative stress is reported to be involved in spermatogenic impairment in Immp2l mutant mice. In this study, we focused on the potential mechanism of Guilingji in protecting the spermatogenic functions in Immp2l mutant mice. The results revealed that Immp2l mutant mice exhibit impaired spermatogenesis and histology shows seminiferous tubules with reduced spermatogenic cells. After administration of Guilingji [150nmol/day/kg intragastric gavage], however, alleviated spermatogenesis impairment and reversed testis histopathological damage and apoptosis. Furthermore, western blotting and the levels of redox classic markers revealed that Guilingji treatments markedly reduced reactive oxygen species. Moreover, Guilingji treatment led to inhibition of the phosphorylation of mitogen-activated protein kinase (MAPK), regulated apoptosis in the cells. In conclusion, the results of the present study suggested that the Guilingji is effective in improving spermatogenesis in Immp2l mutant mice via the regulation of oxidant-antioxidant balance and mitogen-activated protein kinase (MAPK) pathway. Our data suggest that Guilingji could be a promising and compatible antioxidant candidate for the treatment of male infertility.